EkoSonic Thrombolysis as a Therapeutic Adjunct in Venous Occlusive Disease - Zaghlool, D. S. (Int J Angiol, 2016)
The use of ultrasound waves in conjunction with local thrombolysis may accelerate clot resolution and serve as an important therapeutic adjunct in the treatment of venous occlusive disease. Our goal was to provide a larger sample population over a 5-year period to evaluate our experience with the EkoSonic endovascular system (EKOS, EKOS Corporation, Bothell, WA). We suspected that ultrasound-accelerated thrombolysis (UAT) using EKOS would provide excellent thrombolysis and midterm patency rates with minimal thrombolytic complications. A retrospective study was conducted to provide a case series with UAT using EKOS. Data were collected over a 5-year period. Primary end points included degree of thrombolysis. Secondarily, we analyzed thrombolytic usage, complication rates, and midterm patency, over a 1-year period. A total of 48 limbs were treated with UAT. Forty cases were diagnosed as acute, whereas the remaining 8 were chronic. Complete thrombolysis was successful in 38/48 (79%) of patients, and partial thrombolysis was accomplished in 10/48 (21%) of patients. Overall mean infusion time was 22.4 hours ±3.6. There were a total of three complications (6%), all of which were minor bleeding. One-year patency was shown to be 87% with no signs of valvular reflux. UAT using EKOS demonstrated effective rates of thrombolysis with very few complications. In addition, our 1-year patency rates were comparable to published data using conventional catheter-directed thrombolysis. UAT provides lytic therapy by utilizing the benefits of ultrasonic waves to help augment the fibrinolytic process. Our institution currently favors the use of EKOS as the treatment of choice in patients that are appropriate thrombolytic candidates.